Three new species of Peroneutypa (Diatrypaceae, Xylariales) and a first record of Eutypa camelliae in China with updated description - Xinying Mao; Kamran Habib; Rizwana Zulfiqar; Hongde Yang; Yingqian Kang (MycoKeys)
Diatrypaceae is a diverse family with a worldwide distribution, occurring on a wide range of hosts in terrestrial and marine environments, some of which are important plant pathogens. During a survey of ascomycete diversity in Guizhou Province, China, three new taxa within Peroneutypa are proposed based on morphological comparisons and phylogenetic analyses of combined ITS and tub2 sequences data. The newly proposed species are Peroneutypa guizhouensis, P. wanfenglinensis and P. zhujiashanesis. In addition, Eutypa camelliae was recorded for the first time from China, with an updated description. Detailed morphological descriptions, illustrations, comparative analyses, and a tabular comparison of the new species with related and similar taxa are provided.